THE INFLUENCE OF PRICE, PROMOTION, PRODUCT QUALITY ON ONLINE SHOP PURCHASING DECISIONS AMONG STUDENTS - Marlon Batu Bara; Gracia Risky Ester Pakpahan; Evi Inriani Purba; Ester Lasmarito Tobing; Januardin (Jurnal Ekonomi, 2022)
Researchers have a goal to examine whether online shop purchasing decisions among students can be influenced by the quality, promotion, and price of the product in this study. This study uses the SPSS application as data analysis. Researchers used 286 respondents who were students as the research population. Meanwhile, a quantitative approach is used by researchers as a research method. The study findings show that there is a significance of 0.000 and a tcount of 5.093 where the respondent's purchase decision has a significant positive effect on price. On the other hand, there is a significance of 0.000 and tcount of 4.665 which explains that the respondent's Purchase Decision has a significant positive influence by the Promotion. Furthermore, there is a significance of 0.000 and tcount 9, 159 which explains the respondent's purchase decision to have a significant positive effect on product quality. Thus, the researcher concludes that respondents' purchasing decisions are influenced by product quality, promotion, and price